2015
DOI: 10.1038/jid.2014.527
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance Therapy of Adult Vitiligo with 0.1% Tacrolimus Ointment: A Randomized, Double Blind, Placebo–Controlled Study

Abstract: The risk of relapse after successful repigmentation in vitiligo is estimated to 40% within the first year. It has been shown in atopic dermatitis that continuous low-level use of topical corticosteroids and calcineurin inhibitors in previously affected skin can prevent new flares. We hypothesized that a twice-weekly application of 0.1% tacrolimus ointment might be effective for maintaining repigmentation in therapeutically repigmented lesions of vitiligo patients. After randomization, sixteen patients with 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
97
0
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(111 citation statements)
references
References 11 publications
6
97
0
8
Order By: Relevance
“…Therefore, a maintenance therapy remains important to consider in vitiligo management to prevent new episodes of flare‐up as well as accumulation of T RM cells. In this line, it has been clearly demonstrated that the use of topical calcineurin inhibitors as a maintenance therapy twice a week, in patients with repigmented lesions, can reduce the recurrences of previously repigmented vitiligo lesions . These results are consistent with the potential role of the maintenance therapy to dampen the local activation/proliferation of skin resident T RM important for flare‐up of the disease.…”
Section: Looking For Early Intervention In Vitiligosupporting
confidence: 57%
“…Therefore, a maintenance therapy remains important to consider in vitiligo management to prevent new episodes of flare‐up as well as accumulation of T RM cells. In this line, it has been clearly demonstrated that the use of topical calcineurin inhibitors as a maintenance therapy twice a week, in patients with repigmented lesions, can reduce the recurrences of previously repigmented vitiligo lesions . These results are consistent with the potential role of the maintenance therapy to dampen the local activation/proliferation of skin resident T RM important for flare‐up of the disease.…”
Section: Looking For Early Intervention In Vitiligosupporting
confidence: 57%
“…It is worth noting that only 1 out of 15 patients in the present study relapsed during an 8-month follow-up period, while the 1-year relapse rate after treatment is over 30% in other studies [44], mandating that maintenance therapy may be required to sustain the improvements of repigmentation [45]. Moreover, no serious adverse reactions were observed in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…Manual searching found one further article. Of these 19 RCTs matched the selection criteria . Reasons for excluding 58 papers are detailed in Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies were not eligible for meta‐analysis owing to lack of homogeneity. The study from Cavalié et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation